Makroalgae di Paparan Terumbu Karang Kepulauan Anambas - Kadi, Achmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Macroalgae research in Anambas Islands that is the reef flats Jemaja, Pemutus and Matak Waters was carried onJune 2005. Survey method on the research using quadrat transect. Macroalgae is a marine flora which containsChlorophyceae, Phaeophyceae and Rhodophyceae. Biodiversity in the research location was 18 species. Thehigher diversity index (H) was 0.24 and equitability index (e) was 0,105. The higher density of species were 207individuals. Dominant species was 22,83% by Sargassum polycystum.